FEATURES AND CONDITIONS OF SUCCESS OF BUSINESS PROCESS REENGINEERING AT THE ENTERPRISE (Development Service Industry Management, 2024)
The article is devoted to the analysis of the features and conditions of successful reengineering of business processes at enterprises. A thorough review of the literature for a scientific article on the topic of business process reengineering reflects various approaches, methods and research results in this area. The main concepts of business process reengineering (BRP) are considered in the context of adapting enterprises to the changing external environment and increasing their competitiveness. The main principles contributing to the effective implementation of reengineering are considered, such as management readiness for changes, accurate understanding of tasks, control by top management, employee motivation, and the presence of a solid methodological basis. Particular attention is paid to the challenges facing Ukrainian business in the context of current military operations, and the role of reengineering in ensuring its stability and adaptation to new conditions. It is outlined that modern theories and practices of enterprise management require drastic changes, which is caused by the globalization of the world economy, the increasing dynamism of the market environment, and the strengthening of competition. The need to develop new management approaches has been identified, which is connected with transformations in the business itself: the efficiency of enterprises increasingly depends on the implementation of innovations and knowledge embodied in intellectual products; growing competition stimulates the search for new management methods. It is confirmed that in the conditions of modern challenges that are observed at the global level, significant and radical changes that can become a powerful driver of the economic development of enterprises become especially relevant. One of such tools of radical change is the reengineering of business processes. According to the results of this study, approaches to understanding the reengineering of business processes, stages and principles of their implementation were systematized; the essence of reengineering business processes and their practical significance are reflected; analyzed situations in which the company is in a crisis situation and ways to avoid this by means of redesigning business processes
Keywords: business process reengineering; success conditions; enterprise; management; changes; motivation; methodology; business challenges; adaptation